THE EFFECT OF ADDED COARSE SAND FRACTION ON LATERITE SOIL SHEAR STRENGTH - Muhammad Faisal Rijani; Rusdiansyah Rusdiansyah (Universitas Lambung Mangkurat, 2022)
Laterite soil is the most common type of embankment soil used for road construction in Kalimantan. This is because laterite soils are easy to find and widely available in several locations in South Kalimantan. However, this soil has many drawbacks, one of which is that it has a high plasticity index to be used as embankment, both for ordinary embankments and selected embankments. Therefore, it is necessary to improve or stabilize the soil so that the laterite soil can meet the requirements or specifications as embankment soil. In previous studies, the addition of a mixture of sand to laterite soils tends to decrease the value of the plasticity index.This study aims to determine the characteristics of laterite soils and the effect of adding a mixture of sand and plasticity to the shear strength of laterite soils by using a direct shear test apparatus. The specimens were made by testing the standard type of compaction and the value of 90% of the maximum density. The variation of the Sand mixture used is 0%; 7%; 14%; 21%; and 28%.Based on the USCS classification system, the soil for the three preliminary test locations is classified as CH (clay-high) group, while according to the AASHTO classification system, Landasan Ulin and Mandiangin location are classified as group A-7-5 and Sungai Ulin location is classified as group A-7-6 (clayey soils). There was a decrease in the value for the shear strength parameter of the laterite soil from the peak condition to the residual condition. The addition of a mixture of sand in each variation of the sample can reduce the PI value along with the addition of sand. In addition, the addition of sand also changes the parameters of the shear strength of the laterite soil. All samples of laterite and sand mixture variations have a value liquidity index < 0 which indicates that the soil is in a solid or semi-solid condition, while a value consistency index > 0 indicates that the soil is in a solid or semi-solid condition. The higher the value of the plasticity index of a soil, the higher the cohesion value of the soil and the lower the value of the internal shear angle. The more addition of a mixture of sand can reduce the plasticity index and soil cohesion and can increase the value of the internal shear angle. It can be said that the addition of a mixture of sand can reduce the plasticity index of the soil and affect the parameters of the shear strength of the soil in both peak and residual conditions.Keywords: shear strength, residual shear strength, laterite soil, sand, plasticity index